Insights into the antimicrobial potential of Dithiocarbamate anions and metal-based species - Yeo, Chien Ing *; Tiekink, Edward R. T. *; Chew, Jactty * (MDPI, 2021)
Bacterial infection remains a worldwide problem that requires urgent addressing. Overuse and poor disposal of antibacterial agents abet the emergence of bacterial resistance mechanisms. There is a clear need for new approaches for the development of antibacterial therapeutics. Herein, the antibacterial potential of molecules based on dithiocarbamate anions, of general formula R(R’)NCS2(−), and metal salts of transition metals and main group elements, is summarized. Preclinical studies show a broad range of antibacterial potential, and these investigations are supported by appraisals of possible biological targets and mechanisms of action to guide chemical syntheses. This bibliographic review of the literature points to the exciting potential of dithiocarbamate-based therapeutics in the crucial battle against bacteria. Additionally, included in this overview, for the sake of completeness, is mention of the far fewer studies on the antifungal potential of dithiocarbamates and even less work conducted on antiparasitic behavior.